The elusive quest for growth economists' adventures and misadventures in the tropics - Easterly, William 1957- (The MIT Press, 2002)
"Since the end of World War II, economists have tried to figure out how poor countries in the tropics could attain standards of living approaching those of countries in Europe and North America. Attempted remedies have included providing foreign aid, investing in machines, fostering education, controlling population growth, and making aid loans as well as forgiving those loans on condition of institutional reforms." "In this book Easterly shows how these solutions all violate the basic principle of economics, that people - private individuals and businesses, government officials, even aid donors - respond to incentives. Easterly first discusses the importance of growth. He then analyzes the development solutions that have failed. Finally, he suggests alternative approaches to the problem. Written in an accessible, at times irreverent, style, Easterly's book combines modern growth theory with anecdotes from his fieldwork for the World Bank."--Jacket.